An Unusual Case of Stercoral Perforation in a Patient with 86 cm of Small Bowel - Alfin Okullo; Ghiyath Alsnih; Titus Kwok (Case Reports in Surgery)
A 77-year-old male who previously had extensive enterectomy due to ischaemic gut with loss of all but 86 cm of jejunum in addition to a right hemicolectomy presented to the emergency department (ED) with abdominal pain and constipation of 12-day duration. Abdominal imaging with X-ray and CT revealed pneumoperitoneum in addition to a grossly redundant and faecally loaded colon. At laparotomy, rectal perforation was found. In view of the patient’s advanced age, comorbidities, and the absence of intraperitoneal faecal contamination, manual disimpaction followed by wedge resection and primary closure of the perforation was done. On postop day 11, a perforation in the sigmoid colon with free subdiaphragmatic gas was picked up on CT after a work up for abdominal tenderness. In the absence of peritonism and other signs of deterioration, conservative management was chosen with subsequent uneventful recovery for the patient.